2022
DOI: 10.1001/jamadermatol.2022.3234
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Clinical Practice Guidelines for Laser-Assisted Drug Delivery

Abstract: ImportanceLaser-assisted drug delivery (LADD) is used for various medical and cosmetic applications. However, there is insufficient evidence-based guidance to assist clinicians performing LADD.ObjectiveTo develop recommendations for the safe and effective use of LADD.Evidence ReviewA systematic literature review of Cochrane Central Register of Controlled Trials, Embase, and MEDLINE was conducted in December 2019 to identify publications reporting research on LADD. A multidisciplinary panel was convened to draf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…As for infections, it is not recommended for antibiotic or antifungal cases although antiviral when treating the face and genitalia; and antifungal prophylaxis is not recommended [129].…”
Section: Laser Therapymentioning
confidence: 99%
“…As for infections, it is not recommended for antibiotic or antifungal cases although antiviral when treating the face and genitalia; and antifungal prophylaxis is not recommended [129].…”
Section: Laser Therapymentioning
confidence: 99%
“…The depth of these vertical channels is determined by the fluence of the laser 7 . By partially destroying the outer epidermal and dermal layers in a controlled manner, these channels provide a pathway of increased permeability and penetration of various pharmaceuticals 5,7–10 …”
Section: Introductionmentioning
confidence: 99%
“…7 By partially destroying the outer epidermal and dermal layers in a controlled manner, these channels provide a pathway of increased permeability and penetration of various pharmaceuticals. 5,[7][8][9][10] Several studies demonstrated the efficacy of LADD for the treatment of photoaged skin. [10][11][12][13] In recent years, laser-assisted delivery of SQBs has gained tremendous popularity for facial skin remodelling.…”
mentioning
confidence: 99%
“…Such topicals have included analgesics, medications used in photodynamic therapy, 5fluorouracil, corticosteroids, hyaluronic acid, tranexamic acid, and PLLA, among others. 3,4 Cadaveric studies have confirmed that the microchannels created through fractional ablative laser treatment are sufficiently sized for larger-sized PLLA particles (sized 40-63 mm) to pass through the stratum corneum and penetrate the dermis, where they can exert their biologic effects. 1 Topical application of a PLLA suspension immediately following fractional ablative laser treatment has been shown to improve atrophic acne scars and rhytides of the upper lip in patients of FST I-III.…”
mentioning
confidence: 99%